The propagation of mountain waves into the stratosphere: Quantitative evaluation of three-dimensional simulations - Leutbecher, Martin; Volkert, Hans (American Meteorological Society, 2000)
On 6 January 1992 measurements of a mountain wave with significant amplitude were taken over the southern tip of Greenland during an ER-2 flight at an altitude of about 20 km. This work focuses on 3D numerical simulations of the wave generation and its propagation into the stratosphere during this event. The sensitivity of the simulated mountain wave to surface friction and horizontal resolution is explored. A nonhydrostatic model is used for experiments with horizontal resolutions of 12, 4, and 1.3 km. In all simulations the flow over the southern tip of Greenland generates a mountain wave, which propagates into the stratosphere. Changes of surface friction and horizontal resolution affect mostly the amplitude of the mountain wave. Increasing surface friction on the slopes reduces the amplitude of the excited orographic gravity wave. Horizontal diffusion required for numerical stability attenuates gravity waves during their propagation into the stratosphere. Increasing the horizontal resolution permits a smaller diffusion and thereby results in larger stratospheric wave amplitudes. The experiment with increased surface friction at 1.3-km horizontal resolution shows the best agreement with the observational data of the wave in the stratosphere. The differences between the simulated and measured amplitudes of vertical displacement and temperature anomaly are less than about 20%. The disparity in vertical velocity is larger; downward velocities were observed up to 4.8 m s21 and simulated up to 2.7 m s21. In the experiments with lower surface friction at 4-km resolution, the accuracy regarding the amplitude of vertical displacement and temperature anomalies is similar, but the simulated maximum downdraft is even weaker. The other experiments with increased surface friction at 4-km resolution and normal friction at 12-km resolution significantly underestimate the wave amplitude. The results of the experiments suggest that the generation of orographic gravity waves and their propagation into the stratosphere can be ...